1881 Ind. Acts 191, § 82 - (:unkn) unknown (My University, 1881)
Ch. 37, § 82: Prohibited wear or carry of any dirk, pistol, Bowie-knife, dagger, sword-cane, or any other dangerous or deadly weapon concealed, or who carries openly with intent or avowed purpose of injuring another. Violators shall be fined not exceeding five hundred dollars.
Keywords: CARRY - INTENT TO COMMIT CRIME